Preventive Measures Against the Spread of the Plague and the Importance of Preserving Public Health in Serbia in the 18th and First Half of the 19th Century - Nedeljković, Slaviša D.; Đorđević, Miloš Z.; Pešić, Miroslav D. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
After establishing administrations in the newly conquered provinces in southeastern Europe, the Habsburg monarchy formed a sanitary cordon on the border with the Ottoman Empire due to frequent plague epidemics. In the first half of the 18th century, the institution of quarantine was introduced for the first time in Serbia, which included the construction of necessary buildings on the border. The organization of Contumatz, procedures and instructions sent by the Court Sanitary Commission, aimed to act preventively in the protection of the health of the population. The attitude towards science was gradually changing by the end of the century, and published works on the functions, forms and efficiency of braces were read with great care, as well as medical findings of doctors and the proposals for reforming bracelet maintenance methods and isolation methods.Due to the acquisition of the autonomy of the Principality of Serbia according to Haticerif from 1830 and the definition of the border, conditions were created for the formation of a medical service which was in the function of preventing the spread of plague and cholera from the interior of the Ottoman Empire. Special attention was paid to this issue due to the frequent restrictive measures of the Habsburg monarchy on the border  with Serbia, putting Serbian traders in a difficult position. Knez Miloš Obrenović, taking care of the health condition in the principality, was involved in the process of opening quarantine, bringing in doctors, and procuring medicines. Such measures resulted in the suppression of the plague in Serbia, of which there were more in the first half of the 19th century.
Keywords: plague; sanitary cordon; quarantine; Austria; Turkey